STUDY OF MASTITIS IN CAMELS IN ALGERIA - Djeddi Khaled (My University, 2026)
Camels play a crucial role as multipurpose animals, providing milk and meat and serving as a means of transportation. They represent an important financial resource for pastoralists and hold significant cultural and social value. Camel milk, known for its exceptional nutritional properties, is considered a valuable substitute for human milk. However, udder infections, particularly mastitis, pose significant challenges to camel farming.This doctoral research, entitled « Study of Mastitis in Camels in Algeria», aimed to investigate the epidemiological, bacteriological, and therapeutic aspects of mastitis in dairy camels reared under different production systems in southern Algeria, specifically in the regions of Oued Souf and Illizi. A total of 710 she-camels were examined, including 540 camels in Oued Souf 76.05% and 170 camels in Illizi 23.94%. Milk samples collected from lactating she-camels were analyzed using field and laboratory diagnostic methods, including the California Mastitis Test (CMT) and bacteriological culture.The overall prevalence of mastitis reached 31.10%, with subclinical mastitis predominating 27.22% over clinical mastitis (3.88%) in Oued Souf. In contrast, region-specific investigations revealed a clinical mastitis prevalence of 8.75% in BeniGuecha, where the chronic form 6.25% was more frequent than the acute form 2.5%, and 4.70% in southern Algeria (Illizi and Oued Souf).Bacteriological analyses identified Staphylococcus aureus and Streptococcus agalactiae as the predominant pathogens, followed by Escherichia coli, with S. agalactiae accounting for 86% of isolates in clinical cases. Significant risk factors associated with mastitis included udder lesions, the use of anti-suckling devices, tick infestation, poor milking hygiene, age, parity, and stage of lactation. Notably, the use of anti-suckling devices and tick infestation showed a statistically significant association with mastitis occurrence (p < 0.05), and were linked to 71.42% and 85.71% of clinical cases, respectively.Antimicrobial susceptibility testing revealed marked regional variation in resistance patterns: isolates from Oued Souf exhibited multidrug resistance, particularly against oxacillin and oxytetracycline, while penicillin remained the most effective antibiotic. Conversely, isolates from Illizi and southern Algeria showed 100% susceptibility to oxytetracycline, doxycycline, erythromycin, and cotrimoxazole, whereas penicillin and amoxicillin were effective in only 60% of cases, and enrofloxacin showed moderate sensitivity 50%.Economic evaluation demonstrated that mastitis significantly reduced milk yield and altered milk composition, resulting in substantial financial losses for camel herders. Overall, these findings highlight the need for improved hygienic milking practices, effective tick control, rational antibiotic use, and routine antimicrobial susceptibility testing. This research provides a comprehensive understanding of camel mastitis in Algeria and underscores the importance of awareness programs and sustainable control strategies to enhance milk production, animal welfare, and the economic resilience of camel-based production systems.
Les camélidés jouent un rôle crucial en tant qu’animaux polyvalents, fournissant du lait et de la viande, tout en servant de moyen de transport. Ils représentent une ressource financière importante pour les pasteurs et revêtent une valeur culturelle et sociale significative. Le lait de chamelle, reconnu pour ses propriétés nutritionnelles exceptionnelles, est considéré comme un substitut précieux au lait humain. Cependant, les infections mammaires, en particulier la mammite, constituent des contraintes majeures pour l’élevage camelin.Ce travail doctoral, intitulé « Etude des mammites chez la chamelle en algerie », a eu pour objectif d’investiguer les aspects épidémiologiques, bactériologiques et thérapeutiques de la mammite chez les chamelles laitières élevées sous différents systèmes de production dans le sud de l’Algérie, notamment dans les régions d’Oued Souf et d’Illizi.Un total de 710 chamelles a été examiné, dont 540 dans la région d’Oued Souf 76,05 % et 170 dans la région d’Illizi 23,94 %. Des échantillons de lait prélevés chez des chamelles en lactation ont été analysés à l’aide de méthodes diagnostiques de terrain et de laboratoire, notamment le test de Californie (CMT) et la culture bactériologique.La prévalence globale de la mammite a atteint 31,10 %, avec une prédominance de la mammite subclinique 27,22 % par rapport à la mammite clinique (3,88 %) dans la région d’Oued Souf. En revanche, des investigations spécifiques ont révélé une prévalence de la mammite clinique de 8,75 % à Beni Guecha, où la forme chronique 6,25 % était plus fréquente que la forme aiguë2,5 %, et de 4,70 % dans le sud de l’Algérie (Illizi et Oued Souf).Les analyses bactériologiques ont identifié Staphylococcus aureus et Streptococcus agalactiae comme les agents pathogènes prédominants, suivis par Escherichia coli, avec S. agalactiae représentant 86 % des isolats dans les cas cliniques. Les principaux facteurs de risque associés à la mammite comprenaient les lésions de la mamelle, l’utilisation de dispositifs anti-tétée, l’infestation par les tiques, une mauvaise hygiène de traite, ainsi que l’âge, la parité et le stade de lactation. Notamment, l’utilisation de dispositifs anti-tétée et l’infestation par les tiques ont montré une association statistiquement significative avec l’apparition de la mammite (p < 0,05), et étaient liées respectivement à 71,42 % et 85,71 % des cas cliniques.Les tests de sensibilité aux antimicrobiens ont révélé une variation régionale marquée des profils de résistance : les isolats d’Oued Souf présentaient une multirésistance, notamment vis-à-vis de l’oxacilline et de l’oxytétracycline, tandis que la pénicilline demeurait l’antibiotique le plus efficace. En revanche, les isolats d’Illizi et du sud de l’Algérie ont montré une sensibilité de 100 % à l’oxytétracycline, à la doxycycline, à l’érythromycine et au cotrimoxazole, alors que la pénicilline et l’amoxicilline n’étaient efficaces que dans 60 % des cas, et que l’énrofloxacine présentait une sensibilité modérée 50 %.L’évaluation économique a montré que la mammite réduisait significativement la production laitière et altérait la composition du lait, entraînant des pertes financières importantes pour les éleveurs. Dans l’ensemble, ces résultats soulignent la nécessité d’améliorer les pratiques d’hygiène de traite, de renforcer la lutte contre les tiques, d’optimiser l’utilisation des antibiotiques et de recourir régulièrement à des tests de sensibilité antimicrobienne. Cette étude offre une compréhension approfondie de la mammite cameline en Algérie et met en évidence l’importance de programmes de sensibilisation et de stratégies de contrôle durables afin d’améliorer la production laitière, le bien-être animal et la résilience économique des systèmes d’élevage camelin.
Keywords: Algeria– Camels–Mastitis –Resistance – Antimicrobial susceptibility testing – Risk factors; الجزائر– التهاب الضرع– الحساسية للمضادات الحيوية – المقاومة – عوامل الخطر– الناقة.; Algérie – Dromadaire– Facteurs de risque –Mammite –Résistance – Sensibilité antimicrobienne